International Reserve Currencies. (IMF Working Papers; Working Paper ;, 1989)
We study the composition of central bank holdings of foreign reserves when the level of currency riskiness is endogenously determined by economic structure and policymaker preferences in reserve issuing countries. Examination of the behavior of official foreign reserves of the industrial and developing country groups in the period 1977-1984 offers support to the notion that central banks employ mean-variance criteria in selecting international reserves.